Evaluación Presupuestaria aplicada a la Dirección Distrital 19D01–Yacuambi–Zamora MIES del período 2014”. - Suntaxi Guaña, Marcia Cecilia (2016)
The thesis called "BUDGET ASSESSMENT DISTRICT APPLIED TO ADDRESS 19D01-Yacuambi-ZAMORA-MIES PERIOD 2014," it was made because of the importance of the budget in the public sector and financial control. The overall objective in the development of this thesis was based on the budget evaluation of the eight programs of the MIES Zamora District, mission-oriented and provision of public welfare services offered by the MIES, resulting management budgetary satisfactory institutional, is it holds budget allocations, time and cycles, budget for social care of citizens in vulnerable of the Province of Zamora Chinchipe, through the signing of agreements with governments Autonomous Decentralized and private social organizations, thus complying with the objectives and goals planned by that Ministry To determine the degree of efficiency and effectiveness of the annual budget execution Indexes program effectiveness was applied, both in resources and activities, is activities are planned to be developed in each 6 budget program, which must be fulfilled in periods and deadlines included in the Annual Operating Plan (POA). It has also been demonstrated that the planned budget entity has been implemented according to the budget allocations for each program and expenditure group, based on planned activities in each financial period (four months), by applying solvency indicators and Indexes income and expenditure, as well as the indicator analysis of budget reforms, demonstrating the level of budgetary management that keeps the MIES Zamora. From the above it is concluded that the budgetary cycle is fulfilled in the formulation, approval, execution, closure and liquidation of budget, but not the stage of evaluation executed resources is made; also concludes that the Annual Operating Plan is not fully compliant with all its planned activities, due to the numerous budget reforms carried out by the Bank, since the Ministry of Finance (MinFin), does not meet budget allocations within of the periods set out in the Annual Indicative programming. Finally, he surrendered to authorities a report containing conclusions and recommendations of the analysis of the budget of the entity, the same as has been presented for consideration by the highest authority of MIES District Zamora, which will guide timely decision-making, aimed at improving the institutional process management and operation of scheduled future budget plans.